Revisiting Plant Heterosis—From Field Scale to Molecules - Rehman, Attiq ur; Dang, Trang; Qamar, Shanzay; Ilyas, Amina; Fatema, Reemana; Kafle, Madan; Hussain, Zawar; Masood, Sara; Iqbal, Shehryar; Shahzad, Khurram (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Heterosis refers to the increase in biomass, stature, fertility, and other characters that impart superior performance to the F1 progeny over genetically diverged parents. The manifestation of heterosis brought an economic revolution to the agricultural production and seed sector in the last few decades. Initially, the idea was exploited in cross-pollinated plants, but eventually acquired serious attention in self-pollinated crops as well. Regardless of harvesting the benefits of heterosis, a century-long discussion is continued to understand the underlying basis of this phenomenon. The massive increase in knowledge of various fields of science such as genetics, epigenetics, genomics, proteomics, and metabolomics persistently provide new insights to understand the reasons for the expression of hybrid vigor. In this review, we have gathered information ranging from classical genetic studies, field experiments to various high-throughput omics and computational modelling studies in order to understand the underlying basis of heterosis. The modern-day science has worked significantly to pull off our understanding of heterosis yet leaving open questions that requires further research and experimentation. Answering these questions would possibly equip today’s plant breeders with efficient tools and accurate choices to breed crops for a sustainable future.
Keywords: heterosis; hybrid vigor; inbreeding depression; genetic models; molecular basis; crop plants; heterosis; hybrid vigor; inbreeding depression; genetic models; molecular basis; crop plants